2019
DOI: 10.3389/fpls.2019.01356
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes on the Acquisition of Desiccation Tolerance in Seeds of the Brazilian Native Tree Erythrina speciosa

Abstract: Erythrina speciosa Andrews (Fabaceae) is a native tree of Atlantic forest from Southern and Southeastern Brazil. Although this species is found in flooded areas, it produces highly desiccation tolerant seeds. Here, we investigated the physiological and metabolic events occurring during seed maturation of E. speciosa aiming to better understand of its desiccation tolerance acquisition. Seeds were separated into six stages of maturation by the pigmentation of the seed coat. Water potential (WP) and water content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 85 publications
0
12
0
2
Order By: Relevance
“…Similar results were obtained by Jing et al [39], who found that overexpression of galactinol and raffinose synthases was associated with higher concentrations of galactinol, raffinose and stachyose in Arabidopsis mutants than in WT along with enhanced DT in developing mutant seeds. An increase in RFOs accumulation has been recently observed in the orthodox seeds of the Brazilian native tree Erythrina speciosa as well [40]. These results suggest that the increased expression of genes related to the raffinose pathway and accumulation of soluble nonreducing sugars in the cytoplasm during late seed maturation, among other things, might be one of the keys to obtaining DT in seeds.…”
Section: Metabolic Shut-downmentioning
confidence: 54%
“…Similar results were obtained by Jing et al [39], who found that overexpression of galactinol and raffinose synthases was associated with higher concentrations of galactinol, raffinose and stachyose in Arabidopsis mutants than in WT along with enhanced DT in developing mutant seeds. An increase in RFOs accumulation has been recently observed in the orthodox seeds of the Brazilian native tree Erythrina speciosa as well [40]. These results suggest that the increased expression of genes related to the raffinose pathway and accumulation of soluble nonreducing sugars in the cytoplasm during late seed maturation, among other things, might be one of the keys to obtaining DT in seeds.…”
Section: Metabolic Shut-downmentioning
confidence: 54%
“…The results of the initial characterization showed that, although all the fruits had been collected when they were ripe, their embryos showed maturation differences: those of RIB, for example, were closer to physiological maturity than the others, because: a) although the embryos from all regions had very high water content, above 50%, typical for species of the genus Inga (Mata et al, 2013;Schulz et al, 2014), those from RIB had the lowest water potential. This result indicates more binding sites, therefore a better structured matrix (Vertucci and Farrant, 1995); b) the embryos accumulated more dry weight (Marcos-Filho, 2015); c) they had a lower respiration rate, indicating that they were among more mature embryos (the more mature, the lower the respiratory rate, Araujo and Barbedo, 2017) and embryos that had already started germination (the more advanced in germination, the higher the respiratory rates, Hell et al, 2019); d) they had the longest mean germination time, indicating that they had not started germination before harvest, which is relatively common for embryos of this species (Andreo et al, 2006;Bonjovani and Barbedo, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…E, finalmente, as sementes das demais regiões, em posições intermediárias para todas as características, mas com uma curiosa comparação entre JUM e SBC, em que a primeira teve germinação bem mais elevada e, a 35 °C, respiração bem abaixo de SBC. Considerando-se que quanto mais avançado no processo de maturação está a semente, maior o índice de desligamento do metabolismo (Hell et al 2019), há evidente variação no grau de maturação em que as sementes de uma mesma espécie, Eugenia pyrifomris, são dispersas, conforme as condições ambientais.…”
Section: Resultsunclassified
“…Outras sementes recalcitrantes podem, inclusive, iniciar a germinação antes mesmo de sua dispersão, como ocorre em Inga vera, aumentando sua sensibilidade à dessecação e acelerando ainda mais o metabolismo (Caccere et al 2013, Bonjovani & Barbedo 2019, comportamentos que dificultam o armazenamento. Nas sementes tolerantes à dessecação, por sua vez, é evidente a mudança no perfil metabólico na fase que antecede a secagem da maturação, quando há um desligamento das atividades, especialmente as taxas respiratórias (Hell et al 2019).…”
Section: Introductionunclassified